Pengaruh Komunikasi, Motivasi Dan Kompensasi Finansial Terhadap Kinerja Karyawan Bali Safari Dan Marine Park, Gianyar Bali. - Dharma, Norman; Dewi Adnyani, I Gusti Ayu (E-Jurnal Manajemen; Vol 3 No 2 (2014), 2014)
Employee performance at Bali Safari and Marine Park , which is influenced by the communication , motivation and financial compensation either simultaneously or partially is the purpose of this study . The research was conducted at the Company's Bali Safari and Marine Park , with data analysis techniques of multiple linear regression . Number of samples obtained using the Proportionate Stratified Random Sampling method is as much as 85 respondents . Results of the analysis concluded communication motivation and financial compensation have a significant effect on the performance of employees with Fcount value ( 23.974 ) > F ( 2,72 ) . Employee performance as evidenced by the calculation of t exceeds t table by communication , motivation and financial compensation showed partially positive affect . 0,316 value motivational variables on Company the most influence on employee performance.
Keywords: Keywords : Performance , Communication , Motivation and financial compensation